Psychological Self-Actualization analysis of the Russian and Foreign Students - S I Kudinov; S S Kudinov (Peoples' Friendship University of Russia (RUDN University), 2011)
The article discusses the problem of self-actualization of the personality. It also examines separate components of the author's approach to self-actualization. The author's techniques of research of the given phenomenon are described. The comparative analysis of self-actualization of the Russian and foreign students is carried out.